Cover Feature: Diversely Functionalised Cytochalasins through Mutasynthesis and Semi‐Synthesis (Chem. Eur. J. 60/2020). Issue 60 (18th September 2020) - Wang, Chongqing; Lambert, Christopher; Hauser, Maurice; Deuschmann, Adrian; Zeilinger, Carsten; Rottner, Klemens; Stradal, Theresia E. B.; Stadler, Marc; Skellam, Elizabeth J.; Cox, Russell J.
Abstract : A U2OS‐cell triple‐stained for the actin cytoskeleton with a fluorescently‐tagged cytochalasin‐derivative (red) and phalloidin (green) as well as the nucleus (blue) is depicted in the cover image. Cytochalasins are potent ligands of the barbed ends of actin filaments. Here, mutasynthesis was used to create halogenated and azido‐cytochalasins which were then cross‐linked to functional units such as Texas Red and biotin. The new compounds have high utility as new tools for cell biology. More information can be found in the Communication by R. J. Cox et al. on page 13578 .